EP856 Optimal residual disease at primary debulking surgery versus complete tumor resection at interval debulking surgery in advanced epithelial ovarian cancer: a case-control survival analysis. (1st November 2019) - Ghirardi, V; Bizzarri, N; Vargiu, V; D'Indinosante, M; Loverro, M; Pasciuto, T; Scambia, G; Fagotti, A
Abstract : Introduction/Background: Although the non-inferiority in overall survival (OS) of neoadjuvant chemotherapy (NACT) compared to primary debulking surgery (PDS) has been prospectively demonstrated, complete cytoreduction remains the most powerful determinants of survival among patients with stage III–IV epithelial ovarian carcinoma. In this setting, our study aims to compare survival outcomes between patients with 1–10 mm residual disease at primary debulking surgery (PDS) versus those achieving no gross residual disease (NGR) at interval debulking surgery (IDS). Methodology: We retrospectively reviewed patients treated in our Institution from 1/2010 to 12/2016. 151 patients were included. Among them, 50 were allocated in PDS group (Cases) and 101 in IDS group (Controls). Patients were matched for clinicopathologic characteristics and appropriate statistical tests were used. Results: No statistically significant differences were found between the two groups, except for a significant difference in median laparoscopic PIV at time of diagnosis, being lower in the Cases with respect to Controls (p<0.0001). After a median follow up of 55.3 months, 130 (86.1%) progression/recurrences and 72 (47.7%) deaths were registered. Median PFS was 16.0 and 18.3 months for PDS and IDS group respectively (p=0.456); median OS was 48.0 and 60.2 months in for PDS and IDS group respectively (p=0.426). Subgroup analysis for PFS and OS showed no statistically significant difference in relation to patient's age, FIGO stage, laparoscopic predictive index value, surgical complexity score. Conclusion: Our results show that NGR at IDS is associated with the same survival outcomes compared to millimetric residual disease at PDS. In addition, neither older age, nor FIGO stage, and tumour load are correlated with a reduction of survival, irrespectively to the treatment strategy. Research efforts to identify pre-treatment criteria of response to chemotherapy are encouraged to improve patient's treatment selection. Disclosure: Nothing to disclose.